Gilding in Spanish panel painting from the fifteenth and early sixteenth centuries. Issue 2 (2nd July 2016) - Kroustallis, Stefanos; Gómez González, Marisa; Miquel Juan, Matilde; Bruquetas Galán, Rocío; Pérez Monzón, Olga
ABSTRACT: Pure gold is a soft, malleable, and ductile metal. These characteristics allow it to be hammered into thin leaves and applied to other surfaces, a process known as gilding. This study examines the gilding techniques used in Spanish panel and retable painting from the fifteenth to early sixteenth century, considering gold's intrinsic value and symbolism as well as its role as a painting material. First, historical references and laboratory analyses of panel paintings will be compared and interpreted; second, important technical aspects of gold leaf will be discussed, including its composition and possible origin, its thickness and size, its price, and the different poliments and modes of adhesion used to apply it to the substrate.